Corrosion of Iron and Iron Alloys in Seawater - Ekaterina I. Nosova (Археология евразийских степей, 2021)
The article is a review of the latest European research on the problems of iron corrosion in seawater. Such damages are typical for objects of marine archaeology, in particular shipwrecks. For a long time, the study of such corrosion processes was complicated by the fact that samples taken in seawater quickly oxidized in the air and their composition changed significantly. In the early 1980s, after the development of sampling techniques, the study of underwater artifacts corrosion began to develop faster and more efficiently. First of all, the basic processes of iron corrosion and the factors that stimulate them are discussed in the article. These include seawater salinity, oxygen concentration, microbiological activity, pH, temperature, and water circulation patterns, which, in turn, influence the prevalence of other parameters. Next, the iron corrosion products characteristic of the marine environment are described in detail. Finally, the role of microorganisms in the corrosion process and their influence on the preservation of the monument are highlighted.